New Method Evaluation of a Group of 1 Ohm Standard Resistors in National Metrology Institute of Malaysia (NMIM) - et al., Nirul Irwani Ishak (International Journal of Advanced Science and Technology, 2019)
This paper describes the evaluation of a group of 1 W standard resistors in National Metrology Institute of Malaysia. Keeping a group of standard, instead of only one, is one of the best methods to maintain the national standards and ensuring the establishment of the standard’s nominal value with the desired uncertainty. A group of five standard resistor including one externally calibrated standard resistor R1, were arranged to form a network of relationship between the resistors R2, R3, R4 and R5 using the Direct Current Comparator Bridge (DCC Bridge). It has been proven that the mathematical analysis with the measurement method B to preserve a group of 1 W standard resistors is much more reliable and stable than the previous method that use only R1 as a reference resistor. The average value of five standards is assumed to remains constant with time. By using this evaluation, if there is a relatively large change in resistance of the standard, by reference to the average, we will be able to identify which resistor that deviate easily.